Expert System Technology Using Forward Chaining Method to Assess the Risk Level of Diabetic Foot Infection: Original Research - Pratama, Kharisma; Pradika, Jaka; Amrullah, Syahid; Jais, Suriadi (Indonesian Journal of Global Health Research, 2024)
Assessment and care of diabetic feet should always be provided to patients periodically to optimally prevent complications. This necessitates a practical guide that nurses can use to evaluate the risk of wounds in diabetic patients. Previous research has developed protocols for assessing the risk of diabetic foot ulcers; however, these protocols are manual, requiring nurses to spend time determining the risk level of wounds. The aim of this study is to develop a Web-Based Diabetic Foot Infection Risk Scale Application using the Forward Chaining Method. This research utilizes the Stetler model for evidence-based application development. The development process involves three stages: preparation, validation, and analysis. In the first stage, researchers conduct a literature review using literature review protocols and source scientific articles and books, followed by the development of a web-based application using the forward chaining method. There were 19 research articles recruited from three data base scientific (PubMed, Scopus, and Wiley online Library) from 2014-2024. In the second stage, experts will evaluate the content of the application concerning infection risk assessment. Finally, the application is tested. The results of this study have shown that, after testing, the Web-Based Expert System for Diabetic Foot Infection Risk Determination using the forward chaining method can be used and implemented directly by nurses working in diabetic foot care specialty clinics. This research represents an initial stage focusing on assessing infection risk levels, and it is hoped that future research will build upon this study, not only assessing infection risk but also evaluating the potential for diabetic foot ulcers based on assessed risk factors.